Pro Java EE 5 Performance Management and Optimization - Haines, Steven (Apress, 2012)
This book is divided into four parts: • Part 1: Fundamentals • Part 2: Application Life Cycle Performance Management • Part 3: Performance Management in Production • Part 4: Tips and Tricks